Implementation of the Environmental Exploration Learning Model (JAS) Assisted by Google Lens on the Scientific Literacy of Taman Mulia High School Students - Dea Putri Ananda; Mahwar Qurbaniah; Hanum Mukti Rahayu (Postgraduate, University of Mataram, 2024)
This study aims to determine: (1) the difference in science literacy of class X students on plantae material with the Explore Nature Around (JAS) model assisted by google lens, (2) the effect of applying the Explore Nature Around (JAS) learning model assisted by google lens on students' science literacy on plantae material class X Taman Mulia. This type of research is Quasi experiment with Nonequivalent Control Group Design. The population of this study were students of class X Taman Mulia. The sample consisted of two classes determined by random sampling technique. The instruments used consisted of science literacy tests and learning process observation sheets. The data were analyzed by t-test, the analysis was carried out using SPSS version 29.01 for windows which previously conducted homogeneity and normality tests at a significant level of 0.05. Based on the results of the analysis, the conclusions were obtained. (1) The difference in science literacy of class X students on plantae material with the Explore Nature Around (JAS) model assisted by google lens (2) the effect of applying the Explore Nature Around (JAS) learning model assisted by google lens on students' science literacy in plantae material class X Taman Mulia.